Precontrol of the pulmonary artery during thoracoscopic left upper lobectomy and systemic lymph node dissection - Ma, Lin; Mei, Jiandong; Liu, Chengwu; Liu, Lunxu (Journal of Thoracic Disease, 2016)
The main reasons of emergent conversion during thoracoscopic lobectomy included tumor invasion, hilar lymph node (LN) metastasis, and lymphoid tuberculosis. We presented a video which depicted a three-portal thoracoscopic left upper lobectomy with dissection of large LNs. Severe adhesions between a large LN and the first branch of the left pulmonary artery (PA) were found during surgery. For safety reasons, the left main pulmonary artery (LMPA) was clamped with an endoscopic bulldog clamp prior to lymph nodal dissection. The strategy of precontrolling the LMPA during thoracoscopic lobectomy is useful for these patients with complicated hilum, and may assure the safety of the operation.